2007
DOI: 10.1007/s00586-007-0558-9
|View full text |Cite
|
Sign up to set email alerts
|

Scoliosis correction with pedicle screws in Duchenne muscular dystrophy

Abstract: This report describes the spinal fixation with pedicle-screw-alone constructs for the posterior correction of scoliosis in patients suffering from Duchene muscular dystrophy (DMD). Twenty consecutive patients were prospectively followed up for an average of 5.2 years (min 2 years). All patients were instrumented from T3/T4 to the pelvis. Pelvic fixation was done with iliac screws similar to Galveston technique. The combination of L5 pedicle screws and iliac screws provided a stable caudal foundation. An averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 47 publications
3
46
0
Order By: Relevance
“…Pulmonary complications in the peri/postoperative period in DMD patients have been reported to be frequent [1,16,18,21]. Higher pulmonary complications have been reported when the FVC is <30% [7,8,10,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary complications in the peri/postoperative period in DMD patients have been reported to be frequent [1,16,18,21]. Higher pulmonary complications have been reported when the FVC is <30% [7,8,10,19].…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia, respiratory arrest, pneumothorax as well as difficulties in weaning from the respirator have been reported [1,8,16,19,21]. Thus, many surgeons have recommended scoliosis surgery only for patients who have a FVC of at least 35-40% [7,18,21].…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies on the use of pedicle-screws-alone fixation for scoliosis in DMD. Hahn et al [16] reported excellent results for the coronal deformity with 77% correction, both initially and long-term, using pedicle-screwalone fixation to the pelvis (not segmental pedicle screw instrumentation). The mean preoperative curve size in that study was 44°.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pelvic fixation has certain disadvantages, including increased blood loss, longer operative time and technical difficulty [5,10,25,36]. In addition, the sacrum and the pelvis in patients with DMD are often small and osteoporotic [4,16].…”
Section: Discussionmentioning
confidence: 99%
“…Most authors report this technique for the treatment of neuromuscular scoliosis in pediatric patients without additional sacral fixation. Proximal spinal anchorage is done with sublaminar wires [67,71] or with pedicle screws from the L5 level [32,33,72].…”
Section: Iliac Screwsmentioning
confidence: 99%